jurnal PENGARUH VARIETAS DAN JENIS TANAH TERHADAP HASIL CABAI (Capsicum sp.) - Erfyana Putri, Elsha; Heru Pamungkas, Djoko; Arnanto, Driska (JURNAL ILMIAH AGROUST, 2025)
This research aims to determine the effect of variety and soil type on chili growth. This research was conducted at the Self-Help Agricultural and Rural Training Center (PAS) "Lestari Makmur", Jalan Wates Km. 12 Semampir Hamlet, Argorejo Village, Sedayu District, Bantul Regency, Yogyakarta for approximately 60 days. With an altitude of 88 meters above sea level, the soil type is regosol, with a soil pH of 5.5-7, an average temperature of 26-32oC, and rainfall of 1,654 mm/year. The research was arranged in a Completely Randomized Design (CRD), with 2 factorial replications. Factor I chili varieties. Factor II Soil type. Observation variables include plant height, stem diameter measurements, number of flower clusters, number of fruit harbingers, number of fruit per plant, weight of fruit per plant/ha. Analysis of the results using variance at a height of 5% to determine the differences between treatments tested with DMRT (Ducan's Multiple Rage Test). The results of the analysis of variance showed that there was an interaction between the variables measuring stem diameter, number of flower clusters and number of fruit